Effects of exogenous melatonin supplementations on some elemental contents in Anatolian black pine (Pinus nigra J.F. Arnold. subsp. pallasiana (Lamb.) Holmboe) seedling tissues - Yer Çelik, Esra Nurten (BioResources, 2021)
A multi-directional relationship may be conceivable between elements and melatonin in sessile organisms. Melatonin is an important hormone that helps regulate metabolism. This study investigated how different doses (0 μM/control, 250 μM, 500 μM, 1000 μM, and 1500 μM) of exogenous melatonin supplementations (EMS) affected the elemental contents in Anatolian black pine (Pinus nigra Arnold. ssp. pallasiana (Lamb.) Holmboe) seedling tissues (root, stem, and needle). Two different application forms (root-dipping and needle-spraying) were selected in the study. In the samples of seedling tissues, sodium (Na), potassium (K), calcium (Ca), iron (Fe), aluminum (Al), magnesium (Mg)/ppm; chrome (Cr), cobalt (Co), copper (Cu), manganese (Mn), nickel (Ni), phosphorus (P), selenium (Se), silicium (Si), silver (Ag), sulfur (S), zinc (Zn), and molybdenum (Mo)/ppb were analyzed using inductively coupled plasma optical emission spectroscopy (ICP-OES). Of the 18 elements examined, there was a statistically significant difference (p<0.05) between all seedling tissues and different doses of EMS. The results show that EMS may have the regulatory effect on seedling tissue element metabolism.